Robotic-Assisted Hysterectomy for Benign Indications of Uteri Less Than Fourteen Weeks Size Versus More Than Fourteen Weeks Size: A Comparative Study - Bahadur, Anupama (Cureus, 2021)
Objectives This study was conducted to evaluate the feasibility of robotic hysterectomy for benign indications in patients with small size (<14 weeks) versus large size (>14 weeks) uterus. Methods This prospective study was conducted in a single centre from August 2018 to January 2020 in the Department of Obstetrics and Gynecology at All India Institute of Medical Sciences, Rishikesh (Uttarakhand). Surgical outcomes of 216 patients who underwent a robotic hysterectomy in our institution for benign indications were analysed. Women opting for definitive surgical management by minimally invasive technique were divided into two groups according to the size of the uterus less than 14 weeks (group 1) versus more than equal to 14 weeks (group 2). Data collected in both groups included intra-operative and post-operative parameters, length of hospital stay and morbidity if any. Results The demographic profile was comparable in both groups. The mean estimated blood loss was 180.78 ±68.0 ml (range, 10-340 ml) in group 1 and 253.49 ±57ml (range, 60-360 ml) in group 2 (p-value < 0.0001). However, the fall in haemoglobin level after 24 hours of surgery was not statistically significantly different between the two groups. The total duration of surgery in group 1 was 97.86 ± 12.0 minutes (range, 78-132 minutes) and in group 2 was 116.60 ± 15.4 minutes (range, 97-156 minutes), the difference being statically significant (p-value < 0.0001, 95% CI 103±2.1). Console time in group 1 was 43.84 ±6.0 minutes (range, 34-57 minutes) and in group 2 53.22 ±5.5 minutes (range, 44-66 minutes), the difference being statistically significant (p-value < 0.0001, 95% CI 46.57±0.97). There was no difference observed in terms of intra-operative and post-operative complications between the two groups. Conclusion The total duration of surgery and estimated blood loss were directly proportional to the size of the uterus. However, complication rate, hospital stay and requirement of post-op analgesia were comparable in both groups. Robotic surgery in a larger uterus is a feasible option in terms of better surgical outcomes and postoperative course. Thus, robotic hysterectomy in women with a large uterus is a suitable approach in the narrow region of the pelvis.